Biologics for idiopathic inflammatory myopathies. Issue 6 (November 2017) - Moghadam-Kia, Siamak; Aggarwal, Rohit; Oddis, Chester V.
Abstract : Purpose of review: As treatment of refractory cases of idiopathic inflammatory myopathies (IIMs) has been challenging, there is growing interest in assessing novel biologics that target various pathways implicated in the pathogenesis of IIM. Recent findings: In the largest clinical trial in adult and juvenile IIM assessing the effectiveness of rituximab, the primary outcome was not met but 83% of this refractory group of IIM patients met a predefined definition of improvement and rituximab demonstrated a significant glucocorticoid-sparing effect. Antitumor necrosis factor utility in IIM is generally limited by uncertain efficacy data along with recent reports suggesting their potential for inducing systemic autoimmune disease including IIM. Summary: Further research is required to evaluate the role of newer therapies such as tocilizumab (anti-interleukin-6), abatacept (inhibition of T-cell costimulation), sifalimumab (anti-interferonα) and ruxolitinib, (Janus kinase inhibitor) given their biological plausibility and encouraging recent small case series results. Future clinical trials should consider the targeting of biomarkers implicated in the etiopathogenesis of IIM, predictive factors of treatment response, recent revisions in IIM classification criteria, as well as newly developed data-driven response criteria which employ validated core set measures.